Material properties of semiconducting nanostructures synthesized using the chemical bath deposition method - Koao, Lehlohonolo Fortune (University of the Free State (QwaQwa Campus), 2013)
The recent global research interest in wide band gap semiconductors has been focused on zinc oxide (ZnO) due to its excellent and unique properties as a semiconductor material. The high electron mobility, high thermal conductivity, good transparency, wide and direct band gap (3.37 eV), large exciton binding energy (60 meV) at room temperature and easiness of growing it in the nanostructure form, has made it suitable for wide range of applications in optoelectronics, piezoelectric devices, transparent and spin electronics, lasing and chemical sensing. PbS nanostructures is a narrow energy gap material which have relevance for optical applications in the near-IR region of the electromagnetic spectrum such as telecommunications, photovoltaics and bioimaging. It has similar electron and hole effective masses hence the exciton, can be strongly confined which is not always feasible in other semiconductors. Thus the PbS system provides an ideal platform to investigate the exciton in the strong confinement regime. In this thesis, structural and luminescence properties of undoped and doped ZnO and PbS nanostructures (nanorods, nanoflakes, nanoparticles, and nanoflowers) are investigated by different approaches for possible future application of these nanostructures as solar cells and light emitting diodes. Undoped and doped ZnO and PbS nanostructures were grown by chemical bath deposition process. Still it is a challenge for the researchers to produce a stable, reproducible high quality and homogeneously doped ZnO/PbS materials and this seriously hinders the progress of ZnO and PbS nanostructcures to be utilized in various applications. The first part of the thesis includes synthesis of undoped ZnO nanostructures by controlling the growth parameters such as concentrations of precursors (zinc acetate) and synthesis time. Crystalline zinc oxide (ZnO) flower-like nanostructures were synthesized by the chemical bath deposition (CBD) method. The X-ray diffraction (XRD) pattern for the ZnO flower-like microstructures showed crystalline peaks corresponding to a hexagonal wurtzite ZnO structures. Scanning electron microscopy (SEM) observations showed the presence of microcrystallites forming microflower-like aggregates. In the case where a higher molar concentration of zinc acetate was used in the preparation process the microflower-like structures were larger in size than that of the lower mol% used. The shape however did not change. The absorption edges red shifted slightly with an increase in the molar concentration of the zinc acetate and in synthesizing time. The band gap energies decreased slightly with an increase in the molar concentration of the zinc acetate and again in synthesizing time. PL showed that the maximum luminescence intensity was reached at the ZnO synthesized for 5 minutes, any further increase in the synthesizing time resulted into the luminescence intensity decrease. An increase in zinc acetate mol% resulted only in a decrease in luminescence intensity. Controlling growth parameters is important in the sense of controlling the physical, electronic, and chemical properties of materials. In order to understand how to tune these properties in the nanostructure, it is necessary to have an understanding of the growth mechanism that dictates the morphology, structure, and rate of growth of the nanomaterial. The ZnO nanostructures (flower-like rods) were later doped with rare-earth elements (e.g. Ce3+ and Eu3+) and transition metal (e.g. Cu2+). Flower-like hexagonal ZnO:Ce3+ nanostructures obtained for undoped and low mol% of Ce3+. ZnO changed into mixed structure with emergence of pyramids for higher mol% Ce3+. The absorption edges showed that as the molar concentration of Ce3+ ions increases the optical absorption edge shift to a higher. The band gap energies decreased linearly with Ce Concentration. The luminescence bands of undoped ZnO nanoflower-like was quenched and shifted from the yellow region to the blue region when ZnO flower-like was doped with different molar concentration of Ce3+. Eu3+ doped ZnO flower-like structures were synthesized. The XRD spectra of the undoped and low concentration Eu3+ doped ZnO nanostructures correspond to the various planes of a single hexagonal ZnO phase. In contrast with Ce3+ doping, the morphology of the ZnO flower-like rods totally changed to large blocks shape when doped with Eu3+ ions. The effective band gap energy of the ZnO decayed exponentially with the addition of Eu3+. The maximum luminescence intensity was also measured for the same sample. Although weak luminescence was observed for excitation above the band gap at 300 nm the best results were obtained by exciting the Eu3+ directly through the 7F0 → 5L6 absorption band at 395 nm. Excitation at a wavelength of 395 nm produced the highest Eu3+ luminescence intensity without any noticeable ZnO defect emissions. In this work undoped and Cu2+-doped ZnO nanostructures were prepared by the chemical bath deposition (CBD) method. XRD analysis showed the sample prepared were hexagonal ZnO for undoped and Cu-doped. The presence of Cu2+ ions caused the particle size of ZnO flower-like structures to decrease. In the UV-Visible study the reflectance intensity decreased with an increase in the molar concentration of Cu2+ and there was no shift in the absorption edges. The luminescence intensity was found to be a maximum for the undoped ZnO flower-like structures and quenched after addition of Cu2+ ions. In the last part of the thesis, the influence of synthesis temperature and molar concentration of lead acetate on the structure, morphology and optical properties of PbS nanoparticles were investigated. The X-ray diffraction (XRD) peaks correspond to the various planes of a single phase cubic PbS. The surface morphology study revealed nanorod structures at low synthesis temperatures but a particulate structure at the high synthesis temperatures. It was also observed that an increase in the molar concentration of lead acetate has no significant influence on the morphology of the PbS nanorods and the crystallite sizes. The reflectance spectra showed a shift of the absorption edge to a higher wavelength with an increase in the synthesis temperature and molar concentration of Pb acetate. The luminescence intensity was found to decrease with an increase in the synthesis temperature and molar concentration of Pb acetates. The PbS nanoparticles were later doped with Tb3+ and co-doped with Ce3+ ions. When the Tb3+ concentration was increased to 2 mol%, the morphology of the PbS:Tb3+ changed to a mixture of spherical nanoparticles and nanorods. The absorption edges of these PbS nanoparticles slightly shifted to higher wavelength depending on the ionic strength of the precursors. The PL result show an increase in emission intensity with an increase in Tb3+ ions up to 0.3 mol% Tb3+ and decreased there after most probably due to luminescence concentration quenching. A new band at 433 nm was found to emerge as the Tb3+ ions increases. Co-doping PbS nanostructures with 0.3 mol% and 2 mol% Ce3+, the spherical nanoparticles changed the morphology to the nanorods surrounded by the spherical nanoparticle. It was also observed that the size of the nanorods increased with an increase in the molar concentration of Ce3+ ions. The nanoparticles showed good optical properties with high reflectance in the UV and visible regions. The absorption edges shifted to higher wavelength with the addition of Tb3+ and Ce3+, respectively. The photoluminescence results displayed an optimum increase in luminescence intensity when the ratio of Ce:Tb was 1:10 and further increase in cerium content quenched the luminous intensity. It was observed that as the molar concentration of co-dopant (Ce3+) increased the luminescence band at around 433 nm diminished.
Thesis (Ph.D. (Physics))--University of the Free State (Qwaqwa Campus)--University of the Free State, 2013
Keywords: Zinc; Photoluminescence; Nanoparticles; Semiconductors -- Materials; ZnO; PbS; Chemical bath deposition; Spherical; Flower-like; Nanorods; Absorption edges; Defects; Photoluminescence